Study of Wave Dynamics Using Small-Scale Physical Modeling Case Study: Playa Carpayo, Callao-Peru - Tafur, Enrique (2025)
The use of small-scale physical models is a key tool in coastal engineering for representing phenomena such as wave propagation and the effects of coastal structures in breaking zones. This study presents the design and construction of a small-scale physical model applied to Playa Carpayo, located on the coast of Callao, Peru. Vertical and horizontal hydraulic similarity scales of 1:16.7 and 1:180.5, respectively, were used based on Froude similarity, with base maps generated from satellite imagery (Google Earth) and bathymetric data (NAVIONICS and DIHIDRONAV). The model was built in the wave-generating channel of the Laboratory of Hydraulics and Physical Models at EPIMF-FCF-UNMSM, allowing the simulation of wave transformation between T- and L-shaped groynes. Measurements were taken at two representative points: 100 m and 50 m from the prototype shoreline, recording significant wave heights (Hs) of 2.41 m and 1.79 m, respectively. These were compared with the results of the reduced-scale physical model, which yielded Hs values of 2.56 m and 1.88 m. The percentage difference in Hs between the physical model and the prototype was less than 10% in all cases analyzed, confirming the reliability of the developed physical model as an experimental validation tool for coastal dynamics studies.